PENGGUNAAN MODEL PEMBELAJARAN DARING UNTUK MENGHAFAL SURAT PENDEK DI RA AR-RASYID KARTASURA - Isnaini Hadiati, Fauziah; Mila Faila Shofa (Jurnal AUDI: Jurnal Ilmiah Kajian Ilmu Anak dan Media Informasi PAUD, 2024)
At this pandemic era teachers be accused for do learning, the learning that makes it possible for use is online class. Whit the online class, teachers can help students for momorize verse. The purpose of this study was to know about process memorize at the online class and how the teacher deals with the problem come up at the lerning. Research began in September 2020 until August 2021 at RA Ar-Rasyid Kartasura. This type of research is description qualitative, collecting data through observation, interviews and documentation. Data collected than triangulasi method. The results of this study indicate that memorization learning with an online model is going well. The teacher prepares a memorizing lesson plan starting from daily planning to every semester. The target for memorization in the superior class is to be able to memorize juz 30, names of letters 1-60, daily prayers, selected hadiths, and Asmaul Husna. The teacher uses the talqin method in its implementation, WhatsApp Group is used as a learning medium, animated videos, video calls, and rote recordings are used as teaching materials. In one day children memorize one verse. Learning evaluation is carried out in two stages, they are weekly evaluation and semester evaluation. Evaluation is carried out online with children sending videos or voice recordings, while offline evaluations are carried out by scheduling.